Duration, Compliance, and Value of Interdialytic Weight Gain in Chronic Kidney Disease Patients Undergoing Hemodialysis - Muhamad Jauhar; Muhammad Adi Saseno; Umi Faridah (Journal of Bionursing, 2026)
Background: Chronic Kidney Disease (CKD) is a life-threatening problem. CKD patients who require hemodialysis therapy experience a significant increase; one of the important indicators in hemodialysis therapy is interdialytic weight gain (IDWG). In practice, there are still cases where patients experience high IDWG, which is suspected to be due to non-compliance with the schedule or length of hemodialysis sessions. Objectives: This study aimed to determine the relationship between frequency and compliance with the value of IDWG in CKD patients undergoing hemodialysis. Methods: This quantitative study uses a correlative analytical research method with a cross-sectional approach. The population was 47 chronic kidney failure patients undergoing hemodialysis at the Muhammadiyah Mayong Hospital, Jepara. The instruments used were weight scales, patient medical records, and End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ) questionnaires. Bivariate analysis in this study used the Spearman Rho test. Results: The results of this study are that most respondents have undergone hemodialysis for more than 12 months, as many as 20 respondents (42.6%); respondents who are compliant with hemodialysis are 25 respondents (53.2%); and most respondents experienced a mild weight gain category of 16 respondents (34%). There is a relationship between the length of time (p-value = 0.001, r= 0,762) and hemodialysis compliance (p-value = 0.003, r= 0,578) with the interdialytic weight gain value in chronic kidney disease patients undergoing hemodialysis at the hospital. Conclusion: Frequency and compliance have a relationship with the value of IDWG in CKD patients undergoing hemodialysis. The correlation between two variables are direct and positive means that the more compliant with HD, the value of IDWG is lower.